2010
DOI: 10.1016/j.bpj.2010.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cytoskeleton in Controlling the Disorder Strength of Cellular Nanoscale Architecture

Abstract: Cytoskeleton is ubiquitous throughout the cell and is involved in important cellular processes such as cellular transport, signal transduction, gene transcription, cell-division, etc. Partial wave spectroscopic microscopy is a novel optical technique that measures the statistical properties of cell nanoscale organization in terms of the disorder strength. It has been found previously that the increase in the disorder strength of cell nanoarchitecture is one of the earliest events in carcinogenesis. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 49 publications
(66 reference statements)
5
59
0
1
Order By: Relevance
“…It has been shown that there is a strong correlation between the strength of the local morphological distortion ( L md ) in nuclear chromatin structure and the cancer stage, both increase with the progression of carcinogenesis 16 . Therefore, quantification of the strength of the morphological distortion provides the stage or degree of aggressiveness of the cancer in a biological cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that there is a strong correlation between the strength of the local morphological distortion ( L md ) in nuclear chromatin structure and the cancer stage, both increase with the progression of carcinogenesis 16 . Therefore, quantification of the strength of the morphological distortion provides the stage or degree of aggressiveness of the cancer in a biological cell.…”
Section: Resultsmentioning
confidence: 99%
“…The increased nanoscale architectural changes in tumor tissues displaying MUC13 and HER2 interaction depict increased aggressiveness and malignant properties of the tumor 16, 18, 20 . These studies do not provide definitive information about the evaluation of disorder strength due to interaction of MUC13 with HER2.…”
Section: Discussionmentioning
confidence: 99%
“…1(b)] were carried out on a second-generation instrument described in detail elsewhere. 36 Briefly, a plane wave of white light from a xenon lamp (150 W; Oriel, Stratford, CT) is produced by a 4f-lens relay system that focuses onto the sample plane by a low NA ¼ 0.2 condenser lens. Light reflected by the specimen is collected by a NA ¼ 0.4 objective lens (Edmund Optics, Barrington, NJ).…”
Section: Pws Microscopymentioning
confidence: 99%
“…After confirming with AFM that the necessary condition for our algorithm accuracy-precise knowledge of cell thickness-has been satisfied, we measured the intracellular σ n Δ and l c of two genetic variants of human adenocarcinoma HT29 cell lines. Due to their columnar epithelial cell type, 85% to 90% of the measured cell volume 30 was occupied by the cell nucleus, and thus the measured structure was predominantly determined by the nuclear organization of these cells. Results of our analysis showed that while both variants of HT29 cells have a similar RI spatial correlation length l c , the standard deviation of RI within the CV exceeded that in the EGFR-knockdown variant by a factor of 2.…”
Section: Discussionmentioning
confidence: 99%